2015
DOI: 10.1088/0967-3334/36/12/2503
|View full text |Cite
|
Sign up to set email alerts
|

Resonant cavity perturbation: a promising new method for the assessment of total body water in children

Abstract: The accurate measurement of total body water (TBW) in children has important clinical and nutritional applications. Resonant cavity perturbation (RCP) is a new method for estimating TBW. This method measures the dielectric properties of the body which are related to body water. For RCP measurements, each subject lay supine on a bed inside a screened room which acts as a resonant cavity. A network analyser measures the frequencies of two low-order cavity resonances of the room, with electric-field vectors that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…As reviewed in [2], several microwave frequency approaches to hydration monitoring have been previously explored. These include whole body measures using a resonant cavity [15,16], measurements of the skin [17], as well as measurements of the skin and underlying fat layer [18]. In [19], attenuation through the wrist was measured and related to hydration via a complex model.…”
Section: Introductionmentioning
confidence: 99%
“…As reviewed in [2], several microwave frequency approaches to hydration monitoring have been previously explored. These include whole body measures using a resonant cavity [15,16], measurements of the skin [17], as well as measurements of the skin and underlying fat layer [18]. In [19], attenuation through the wrist was measured and related to hydration via a complex model.…”
Section: Introductionmentioning
confidence: 99%
“…Various researchers have found that the shape factor can be reduced by combining measurements with the test object in two or more orientations, e.g. Kraszewski and Nelson (1990) looking at seeds, and Oldroyd et al (2015) measuring total body water (TBW) in human subjects. In this paper we demonstrate a novel method of removing the shape factor completely, by comparing to an object of the same shape and known dielectric properties, as illustrated in Figure 1.…”
Section: Introductionmentioning
confidence: 99%